2001
DOI: 10.1385/jmn:17:3:379
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Understanding of Biological Role of Colostrinin Peptides

Abstract: The aim of this study was to elucidate the structure and possible function of colostrinin, also known as a proline rich polypeptide (PRP). The molecular weight of colostrinin was originally determined by gel filtration to be 17,200 daltons. In the presence of guanidinum chloride, however, the molecular weight was found to be about 6,000 daltons. Further studies utilizing high-performance liquid chromatography (HPLC) and mass spectroscopy revealed that colostrinin is a complex consisting of many low molecular-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 14 publications
2
30
0
Order By: Relevance
“…CLN is a mixture of low-molecular-weight, proline-rich peptides [2, 4, 5] that has been administered to individuals with age-associated dementia [12,13,14]. Whether CLN induces allergic responses or modulates responses to other allergens has never been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CLN is a mixture of low-molecular-weight, proline-rich peptides [2, 4, 5] that has been administered to individuals with age-associated dementia [12,13,14]. Whether CLN induces allergic responses or modulates responses to other allergens has never been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…CLN is purified from pre-milk fluid (colostrum) collected from mothers during the first 24 h after giving birth [1,2,3,4,5]. It has been shown that CLN is an important immune modulator that induces maturation and differentiation of murine thymocytes [3, 6], promotes peripheral blood leukocyte proliferation and induces cytokine production [3, 7].…”
Section: Introductionmentioning
confidence: 99%
“…CLN was purified from ovine (CLN O ) or bovine (CLN B ) colostrum as described previously (Janusz et al, 1974;Kruzel et al, 2001Kruzel et al, , 2004. Two-dimensional acrylamide gel electrophoresis showed that the protein (3-25 kD polypeptides) composition of CLN O and CLN B was nearly identical in size and number (Boldogh et al, unpublished data).…”
Section: Colostrininmentioning
confidence: 99%
“…144 During a preliminary trial of the putative immunomodulatory effects of proline-rich polypeptide, unexpected psychostimulation was observed in human subjects. 145 Subsequently, trials in rats demonstrated that administration of clostrinin, a specific proline-rich polypeptide preparation, promoted spatial learning and improved incidental memory, 146 leading to the proposal that proline-rich polypeptide attenuates neurologic decline.…”
Section: Multifunctional Casein Peptidesmentioning
confidence: 99%